Comparative study on ultrasonic placental grading among normotensive pregnancy and pregnancy-induced hypertension and its correlation with fetal outcome - Pratima Garain; Sannyasi Charan Barman; Priyanka Mandal; Patra, Kajal Kumar; Kishore P Madhwani (Asian Journal of Medical Sciences, 2024)
Background: Placenta is essential for the fetal well-being, growth, and development which can be evidenced as early as possible through ultrasound at 6 weeks of gestation. The placenta mediates the intrauterine interaction between a mother and her baby. Aims and Objectives: This study aims to compare the pattern of placental grading among normotensive and pre-eclampsia mothers in a tertiary care hospital. Materials and Methods: This hospital-based observational analytical study has been conducted in the labor ward and outpatient department of the Department of Obstetrics and Gynaecology, Bankura Sammilani Medical College and Hospital from April 2021 to September 2022. A total of 69 pre-eclampsia mothers (study group) and 69 normotensive mothers (control group) who fulfill inclusion and exclusion criteria were included in the study. Template was generated and analysis was done on Statistical Package for the Social Sciences software. Results: A total of 138 pregnant women with 69 pregnant normotensive and 69 pregnant preeclampsia mothers were included in the study. The mean age of the study participants was 21.3 years (standard deviation=3.6). About 81.2% and 89.9% of the normotensive and hypertensive mothers, respectively, resided in rural areas. Cesarean/instrumental delivery was higher among the hypertensive pregnant women (42.0%) when compared to normotensive pregnant women (27.5%) and it was found to be statistically significant. Birth asphyxia was observed to be higher among the neonates in the hypertensive group (15.9%) when compared to the normotensive group (4.3%) and it was found to be statistically significant. Neonatal intensive care unit admission was more among the neonates of the mother with hypertension and it was found to be statistically significant. There was no significant difference in the birth weight of the newborn with the placental grading among the normotensive pregnant women. Conclusion: Ultrasonographic placental grading could be used as a screening tool for antepartum fetal surveillance in the obstetric population. Placental grading will help us to early diagnosis and to formulate line of management and timely intervention to reduce maternal and perinatal complications.